Indigenous fungal plant pathogen as biocontrol agent for goosegrass (Eleusine indica) in oil palm plantation - Ismail, Maizan; Juraimi, Abdul Shukor; Rusli, Mohd Hefni; Abu Seman, Idris; Husri, Mohd Naqiuddin (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Goose grass (Eleusine indica) is a noxious weed in orchards and oil palm plantations in Malaysia. The weed is listed as one of the 10 worst weeds of the world as it competes strongly with the main crop for nutrient, water, light and space. Currently, farmers and planters are applying herbicide as an effective method to control E. indica in the field, however the overused of chemical herbicides has led to the incidence of herbicide resistance especially on glyphosate. Therefore, an alternative method using the indigenous plant pathogens as biocontrol agents for E. indica has been carried out. The method is environmental friendly. Three different species of indigenous plant pathogens from E. indica diseases namely Bipolaris sorokiniana, Phoma herbarum and Curvularia aeria were screened to test the pathogenicity to E. indica. Results of pathogenicity test have shown that B. sorokiniana is highly pathogenic to E. indica with the highest rating of disease severity percentage among all tested fungal pathogens. B. sorokiniana infected E. indica at day five after the artificial inoculation with 2 x 106 cfu/mL + 0.01% TWEEN 20 and was rating as highest disease severity compared to P. herbarum and C. aeria after 40 days of treatment. B. sorokiniana also resulted in the lowest dry weight of biomass which is a good indicator of retarding E. indica growth. Study on host range test has resulted that B. sorokiniana did not affect any of the important crops tested but consistently infected E. indica in the test.